COLLABORATIVE CLASSROOM MANAGEMENT AND THE ROLES OF LEAD AND ASSISTANT TEACHERS IN EARLY CHILDHOOD EDUCATION: A CASE STUDY AT RA YAA BUNAYYA, PAPUA - Ubaidillah, A; Maryati, Sulis (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Effective classroom management plays a vital role in Early Childhood Education (ECE) to support children’s cognitive, social-emotional, and behavioral development. This study explores collaborative classroom management through co-teaching practices between lead and assistant teachers at RA Yaa Bunayya, Papua. Purpose: It aims to examine the interaction, division of responsibilities, and contributions of both roles in creating an inclusive and supportive learning environment. Method: A qualitative case study was conducted using participatory observations, in-depth interviews, and document analysis involving two lead teachers, two assistant teachers, and the school principal. Result: Thematic analysis revealed that lead teachers focused on core learning activities, while assistant teachers provided individual support, maintained classroom order, and supervised children. Collaboration occurred during the planning, implementation, and evaluation stages, facilitated by open communication and clearly defined roles. Challenges such as role ambiguity and time constraints were addressed through professional training and administrative support. Conclusion: The findings affirm that co-teaching enhances classroom climate, child engagement, and instructional effectiveness. Implication: This study offers empirical insights for developing collaborative teaching models in ECE and suggests directions for future research on co-teaching implementation across diverse educational contexts in Indonesia.